Trace element distribution in marine microplastics using laser ablation-ICP-MS. (November 2020) - El Hadri, Hind; Gigault, Julien; Mounicou, Sandra; Grassl, Bruno; Reynaud, Stéphanie
Abstract: Due to the dramatic quantity of plastic debris released into our environment, one of the biggest challenges of the next decades is to trace and quantify microplastics (MPs) in our environments, especially to better evaluate their capacity to transport other contaminants such as trace metals. In this study, trace elements (Fe, Cu, Zn, As, Cd, Sn, Sb, Pb, and U) were analyzed in the microplastic subsurface (200 μm) using laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). Microplastics subjected to the marine environment were collected on beaches (Guadeloupe) exposed to the north Atlantic gyre. We established a strategy to discriminate sorbed contaminants from additives based on the metal concentration profiles in MP subsurface using qualitative and quantitative approaches. A spatiotemporal correlation of the sorption pattern was proposed to compare MPs in terms of relative exposure time and time-weighted average concentrations in the exposure media. Graphical abstract: Unlabelled Image Highlights: Analyses of trace elements concentration distribution in the subsurface of microplastics Discrimination between sorbed trace elements and additives in environmentally exposed microplastics Assessment of exposure time of microplastics in the marine environment Evaluation of time-weighted average concentration of trace elements in the exposure media